Open versus selective customer loyalty programmes. Issue 5 (9th May 2016) - Esmark, Carol L.; Noble, Stephanie M.; Bell, John E.
Abstract : Purpose: This paper aims to examine the impact of an open loyalty programme (anyone can join) versus a selective programme (requirements must be met) to show what types of loyalty programmes are most effective. In-group identification, gratitude, stage of relationship and visibility are additionally examined. Design/methodology/approach: Two studies use experimental methodology to initially test the relationships. A third study uses survey and panel data. Findings: Open programmes lead to more in-group identification, while selective programmes lead to higher levels of gratitude, especially in mature stages. Visible programmes lead to more in-group identification. Industry differences are presented. Research limitations/implications: The first two studies use a student sample (although Study 3 uses penal data). The research is limited to the variables examined. The findings add to theory by showing differences between open and selective loyalty programmes. Practical implications: The findings show how different retailer offerings change the value and experience to the customer leading to loyalty intentions. Loyalty programme designers can tailor their programme structure to fit their customers and overall strategy. The findings also shed light on the strategic importance of tiered loyalty programmes. Originality/value: The examination of how a customer enters a loyalty programme is not in current literature. The research shows how loyalty intentions are impacted by design of the programme, including how a customer signs up for a programme. The mechanisms through which the relationship works increase the understanding of loyalty programme effectiveness.